Efficient native strains of rhizobia improved nodulation and productivity of French bean (Phaseolus vulgaris L.) under rainfed condition - Athul, Puthan Purayil; Patra, Ranjan Kumar; Sethi, Debadatta; Panda, Narayan; Mukhi, Sujit Kumar; Padhan, Kshitipati; Sahoo, Sanjib Kumar; Sahoo, Tapas Ranjan; Mangaraj, Satyabrata; Pradhan, Shriram Ratan; Pattanayak, Sushanta Kumar (Frontiers in Plant Science, 2022)
The biological nitrogen fixation is a most important ecofriendly approach of nitrogenous fertilizer management in rhizosphere. The Rhizobium is the most important symbiotic N-fixer. Native strains of Rhizobium perform better than the non-native strains by getting ambient condition for growth and proliferation. Native strains enhance the soil fertility and productivity of pulses. The study was carried out in three phases, i.e., pot experiment, field experiment, and farmer’s field demonstrations. In a pot experiment two isolated rhizobia were inoculated to seeds of French bean (Phaseolus vulgaris), applied with and without lime to evaluate crop growth, photosynthetic activity, and nodule characteristics of target crop. In field, strains were inoculated to seeds of French bean, which received different combinations of inputs; inorganic fertilizers, lime and boron to study the influence of native stains on crop productivity and agronomic efficiency. The photosynthetic activity, root, shoot and nodular characteristics were significantly higher in soil receiving lime treatment than no limed one. The inoculation of native rhizobia strains with liming to acid soil increased 46% to 72% of leaf nitrogen content over non-limed rhizobia inoculated packages. In field experiment adoption of soil test-based fertilizers application had advantage of 25 % in pod yield over farmer’s practice. Acid soil amelioration with lime improved pod yield ranging from 14 to 39 %. Farmer's field demonstration recorded highest pod yield in the package where seeds were inoculated with S2 (RBHR-21) strain added with soil test-based fertilizers (STD) followed by STD +S1 (RBHR-15) with 98 and 84 % increase over farmer’s practice. However, experimental evidence favored using both strains for bio-inoculation of French bean crop.